LESSONS FROM VIETNAM’S SOLAR POWER PLANT GROWTH DEVELOPMENT FOR INDONESIA TO REACH NET ZERO EMISSION: Pembelajaran Pertumbuhan PLTS Vietnam bagi Tantangan Indonesia Menuju Net Zero Emission - Irwan Wakhidiyanto (Jurnal Nasional Pengelolaan Energi MigasZoom, 2022)
CO2 gas emissions are increasingly massive, one of which is caused by the generation of energy from fossils in many countries that poses a threat to climate change. The global world has agreed on the Paris Agreement in 2016 to reduce carbon emissions in 2050. ASEAN countries are also taking concrete steps, especially in the electricity sector by seeking renewable energy sources. At present Vietnam has succeeded in becoming the leading country in ASEAN in the solar power development sector in order to meet its electricity needs and also in order to reduce carbon emissions. Indonesia is one of the countries that has ratified the agreement has made a "grand strategy" for the development of solar power plant which aims to reduce the use of fossil energy and national carbon emissions by 2060. This paper aims to provide a comparative study between Vietnam and Indonesia in terms of policy and implementation of solar power plant development to date. The methodology that the authors use in this study is a qualitative research with a descriptive approach to provide a holistic picture. The method of this study applied two steps, i.e. systemic literature review and comparative observation between Vietnam and Indonesia. The data obtained was also reviewed from state documents, academic literature, to media bold that are relevant to this research. Conclusively, the author managed to review that Vietnam is far more successful with several advantages that Indonesia can emulate which is still hampered from developing solar power plant in the near future.